TEACHING WRITING HISTORICAL RECOUNT TEXT USING GOOGLE CLASSROOM - Al Hadad, Alawi; Irmayani, Irmayani; Khulel, Buyun (MEDIA DIDAKTIKA, 2024)
Google Classroom is a tool that facilitates students and teacher collaboration also the teacher can make and distribute assignment for students in an online classroom for free.In this research, the researcher focuses on analyzing the way the teacher teaches recount text using Google classroom start from the teacher prepare the lesson plan until the teacher give the assignment. There are some steps that the researcher will observe and explain from the teacher prepares the lesson, the teacher makes and prepares Google Classroom, the teacher prepares the material about historical writing recount using Google classroom and the teacher gives the task and assignment. This research is conducted by using descriptive-qualitative method. The data in this research are analyzed in the form of world description and identification or analysis. By using descriptive-qualitative method, the researcher presents the data description of this research based on the result of the researcher’s experience in doing teaching practice. Besides that, the researcher also presents data description based on observation and interview. Data in this research is qualitative data that are written through words by words, including statements or dialogue in the form of descriptive or narrative as the data are taken from interview transcript, observation sheet, and field note. Google classroom is proved by another researcher as the one of the most used platforms to bypasses the traditional learning activity be an alternative online learning platform to be used in the classroom.